2021
DOI: 10.4236/jwarp.2021.134018
|View full text |Cite
|
Sign up to set email alerts
|

Water Productivity of Poplar and Paulownia on Two Sites in Kyrgyzstan, Central Asia

Abstract: As Central Asia is a region with wide spread water scarcity as a result of excessive irrigation of agriculture, land use changes deserve research about potential impacts on the already strained water resources. Poplars have a long tradition as agroforestry tree across Central Asia, while paulownia is new to the region, but has been gaining extreme attention as a potential plantation and/or agroforestry tree. Therefore, the water productivity of those two tree species is investigated here on 3-year-old trees, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In recent reports, Iran, due to its field experience, has reported its ability to plant Paulownia in an area of approximately 16 × 10 4 km 2 (Galán-Martín et al, 2015;Abbasi et al, 2020). More importantly, several nations are beginning to advance in this area, such as Portugal (Abreu et al, 2020), Iran (Abbasi et al, 2020), Spain (Parra-Lopez et al, 2015;Pleguezuelo et al, 2015), Romania (BUZAN et al, 2018), Italy (Testa et al, 2022), Serbia (Janjić and Janjić, 2019), Ukraine (Morozova et al, 2020;Kaletnik et al, 2021), Northern Ireland (Woods, 2008a;Olave et al, 2015), and Kyrgyzstan (Thevs et al, 2021).…”
Section: Paulownia As a Sustainable Model For Co 2 Mitigationmentioning
confidence: 99%
“…In recent reports, Iran, due to its field experience, has reported its ability to plant Paulownia in an area of approximately 16 × 10 4 km 2 (Galán-Martín et al, 2015;Abbasi et al, 2020). More importantly, several nations are beginning to advance in this area, such as Portugal (Abreu et al, 2020), Iran (Abbasi et al, 2020), Spain (Parra-Lopez et al, 2015;Pleguezuelo et al, 2015), Romania (BUZAN et al, 2018), Italy (Testa et al, 2022), Serbia (Janjić and Janjić, 2019), Ukraine (Morozova et al, 2020;Kaletnik et al, 2021), Northern Ireland (Woods, 2008a;Olave et al, 2015), and Kyrgyzstan (Thevs et al, 2021).…”
Section: Paulownia As a Sustainable Model For Co 2 Mitigationmentioning
confidence: 99%
“…The water productivity of paulownia and poplar in Kyrgyzstan was studied by N. Thevs et al (2021). These studies were conducted to identify the possibility of additional load on water resources of the introduced paulownia (Paulownia tomentosa × fortunei) compared to three-year-old poplar (Populus deltoides × nigra) plants.…”
Section: Introductionmentioning
confidence: 99%
“…The stem biomass of paulownia increased by 4.8 kg at an average flow rate of 2.36 l/day (water productivity 11.90 g/l). Therefore, N. Thevs et al (2021) concluded that the reproduction of paulownia will not put more pressure on the water resources of Central Asia than poplar. This refutes the negative feedback that paulownia is an invasive species and has a negative impact on other tree species.…”
Section: Introductionmentioning
confidence: 99%